2019
DOI: 10.1038/s41598-019-55538-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy was associated with the lower incidence of metachronous second primary lung cancer

Abstract: Our study aims to estimate the incidence of metachronous second primary lung cancer(SPLC) in initial primary lung cancer(IPLC) survivors and to determine whether radiotherapy affects the risk of metachronous SPLC in the first five years after the diagnosis of lung cancer. Incidence data of IPLC individuals who survived ≥2 years were obtained from SEER-18 database in 2004–2007. Joinpoint regression analysis and competing risk analysis were used to calculate the incidence of metachronous SPLC. Propensity score m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
8
1
3
Order By: Relevance
“…Thakur et al demonstrated a higher risk of developing a second lung cancer in patients with previously treated lung cancer (7). Although many studies also concluded that radiotherapy was significantly associated with an increased incidence of second lung cancer, longterm follow-up results did not support the association in studies by our group and others (9,20,21).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Thakur et al demonstrated a higher risk of developing a second lung cancer in patients with previously treated lung cancer (7). Although many studies also concluded that radiotherapy was significantly associated with an increased incidence of second lung cancer, longterm follow-up results did not support the association in studies by our group and others (9,20,21).…”
Section: Discussioncontrasting
confidence: 54%
“…Similar to our results, one previous study assessed the risk of second thoracic cancer following the diagnosis of the initial lung cancer and found that radiotherapy was significantly associated with an increased risk of second primary esophageal cancer when the latency was set as ≥5 years, but no such significant difference was observed for second primary lung and breast cancers (20). The studies from both Hu et al and Abdel-Rahman et al reported that radiation therapy was significantly associated with a lower incidence of a metachronous second primary lung cancer within 5 years after the diagnosis of the initial lung cancer (20,21). However, in contrast to our study, Berrington de Gonzalez et al concluded that lung cancer patients receiving radiation therapy had an increased risk of developing SPM (9).…”
Section: Discussionmentioning
confidence: 99%
“…The primary tumor control rate of SRS is 97.6% in medically inoperable early-stage non-SCLC [ 8 ]. Recently, the risk of metachronous MPLC was found to be lower with radiotherapy than non-radiotherapy [ 6 , 8 ] even though in stage IA lung cancer [ 5 ]. The incidence of metachronous MPLC was 0.5% at 1 year and 2.28% at 5 years among solitary PLC survivors with radiotherapy, which was lower compared to the non-radiotherapy group [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the risk of metachronous MPLC was found to be lower with radiotherapy than non-radiotherapy [ 6 , 8 ] even though in stage IA lung cancer [ 5 ]. The incidence of metachronous MPLC was 0.5% at 1 year and 2.28% at 5 years among solitary PLC survivors with radiotherapy, which was lower compared to the non-radiotherapy group [ 6 ]. Based on these findings, it is assumed that the SRSs might not induce metachronous MPLC in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation